2020
DOI: 10.1212/nxi.0000000000000710
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 promoter (GT) n polymorphism associates with HIV neurocognitive impairment

Abstract: ObjectiveTo determine whether regulatory variations in the heme oxygenase-1 (HO-1) promoter (GT)n dinucleotide repeat length could identify unique population genetic risks for neurocognitive impairment (NCI) in persons living with HIV (PLWH), we genotyped 528 neurocognitively assessed PLWH of European American and African American descent and linked genotypes to cognitive status.MethodsIn this cross-sectional study of PLWH (the CNS HIV Antiretroviral Therapy Effect Research cohort), we determined HO-1 (GT)n re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…We concluded that HIV infection and HIV-driven neuroinflammation and immunoproteasome induction could lead to accelerated HO-1 protein degradation and loss, leading to neuronal injury and, ultimately, HIV-NCI. Finally, we also showed that the HO-1 gene promoter region (GT) n dinucleotide repeat genetic variation, which is known to modulate HO-1 transcriptional activity, associates with a risk of HIV-NCI and neuroinflammation in PLWH in a pattern consistent with a role for HO-1 in reducing risk of HIV-NCI (Garza et al 2020;Gill et al 2018). We thus hypothesized that PLWH have HIV-driven neuroinflammation and immunoproteasome expression throughout the brain that associates with HO-1 expression, and that this might associate with synaptic integrity in multiple regions, or even predominantly in selected regions.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We concluded that HIV infection and HIV-driven neuroinflammation and immunoproteasome induction could lead to accelerated HO-1 protein degradation and loss, leading to neuronal injury and, ultimately, HIV-NCI. Finally, we also showed that the HO-1 gene promoter region (GT) n dinucleotide repeat genetic variation, which is known to modulate HO-1 transcriptional activity, associates with a risk of HIV-NCI and neuroinflammation in PLWH in a pattern consistent with a role for HO-1 in reducing risk of HIV-NCI (Garza et al 2020;Gill et al 2018). We thus hypothesized that PLWH have HIV-driven neuroinflammation and immunoproteasome expression throughout the brain that associates with HO-1 expression, and that this might associate with synaptic integrity in multiple regions, or even predominantly in selected regions.…”
Section: Discussionmentioning
confidence: 55%
“…We found significant associations between this polymorphism and type I IFN-stimulated genes and T lymphocyte activation within the prefrontal cortex of PLWH (Gill et al 2018). In a separate clinical cohort study of PLWH, we observed modulating effects of the HO-1 (GT) n promoter dinucleotide repeat on risk of HIV-NCI (Garza et al 2020). These observations suggest a balance between transcriptional and post-translational mechanisms of HO-1 modulation that determine parenchymal HO-1 levels in the setting of neuroinflammation in the prefrontal cortex, and they also suggest a role for HO-1 expression in modulating risk of HIV-NCI.…”
Section: Introductionmentioning
confidence: 63%
“…With regard to the viral infections, recent data showed a lower risk of HIV-induced neuroencephalitis and neurocognitive impairment in patients with S allele [ 46 , 135 ]. Seu et al [ 136 ] reported high viral loads and soluble CD14 in HIV-infected patients on antiretroviral therapy having the L allele.…”
Section: Ho-1 Genetic Polymorphism and Disease Severitymentioning
confidence: 99%
“…Specifically, longer (GT) n repeats are associated with low levels of HO-1 expression ( 21 ) and correlate with higher disease susceptibility, while shorter (GT) n repeats are associated with higher levels of HO-1 expression and correlate with lower disease susceptibility. This has been illustrated for cardiovascular disease ( 25 28 ), chronic kidney disease ( 29 , 30 ), HIV-induced central nervous system neuroinflammation ( 31 , 32 ), rheumatoid arthritis ( 33 ), chronic obstructive pulmonary disease ( 34 ), and organ transplantation ( 35 , 36 ). In sharp contrast, however, shorter (GT) n repeats are associated with higher levels of HO-1 expression and promote metaflammation associated with the onset of experimental metabolic disease ( 37 ).…”
Section: Introductionmentioning
confidence: 99%